2020
DOI: 10.1016/j.jbior.2019.100651
|View full text |Cite
|
Sign up to set email alerts
|

Altered chondrocyte differentiation, matrix mineralization and MEK-Erk1/2 signaling in an INPPL1 catalytic knock-out mouse model of opsismodysplasia

Abstract: and its different differentiation steps. Finally, we identified a role of osteocalcin in mineralized nodules production and for the MEK-Erk1/2 signaling pathway in the OPS phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Nevertheless, it has been demonstrated that 5-phosphatases, such as Src homology 2-containing inositol 5-phosphatase (SHIP) in hematopoietic cells [8], Phosphatidylinositol 4,5-Bisphosphate 5-Phosphatase (PIB5PA) in neuritis and melanoma cells [9,10], and Src homology 2-containing inositol 5-phosphatase 2 (SHIP2) in glioblastoma and GC cells, inhibit Akt activation [11,12]. SHIP2, encoded by inositol polyphosphate phosphatase-like 1 (INPPL1), belongs to the phosphoinositide 5-phosphatase family, which has been implicated in some human diseases such as type 2 diabetes, Alzheimer's disease and Opsismodysplasia [13][14][15]. However, the role of SHIP2 in tumorigenesis and tumor progression remains paradoxical: high SHIP2 expression has been found in breast cancer, hepatocellular cancer, non-small cell lung cancer, and colorectal cancer, which correlates with poor survival of patients and contributes to the malignant potential of these tumors [16][17][18][19], whereas reduced expression of SHIP2 in GC promotes tumorigenesis and proliferation of GC via activation of the PI3K/Akt signaling [12], and, in squamous cell carcinoma and glioblastoma cells, SHIP2 inhibits Akt activation and leads to apoptosis and cell cycle arrest [11,20].…”
mentioning
confidence: 99%
“…Nevertheless, it has been demonstrated that 5-phosphatases, such as Src homology 2-containing inositol 5-phosphatase (SHIP) in hematopoietic cells [8], Phosphatidylinositol 4,5-Bisphosphate 5-Phosphatase (PIB5PA) in neuritis and melanoma cells [9,10], and Src homology 2-containing inositol 5-phosphatase 2 (SHIP2) in glioblastoma and GC cells, inhibit Akt activation [11,12]. SHIP2, encoded by inositol polyphosphate phosphatase-like 1 (INPPL1), belongs to the phosphoinositide 5-phosphatase family, which has been implicated in some human diseases such as type 2 diabetes, Alzheimer's disease and Opsismodysplasia [13][14][15]. However, the role of SHIP2 in tumorigenesis and tumor progression remains paradoxical: high SHIP2 expression has been found in breast cancer, hepatocellular cancer, non-small cell lung cancer, and colorectal cancer, which correlates with poor survival of patients and contributes to the malignant potential of these tumors [16][17][18][19], whereas reduced expression of SHIP2 in GC promotes tumorigenesis and proliferation of GC via activation of the PI3K/Akt signaling [12], and, in squamous cell carcinoma and glioblastoma cells, SHIP2 inhibits Akt activation and leads to apoptosis and cell cycle arrest [11,20].…”
mentioning
confidence: 99%
“…MAPK3 was discovered as a particularly interesting candidate gene for outer ear development of lop eared pigs, known to play an essential role in the MAPK/ERK cascade, which mediates various biological processes such as cell growth, adhesion, survival and differentiation by regulating transcription, translation and rearrangements of the cytoskeleton [ 53 ]. Furthermore, MAPK was shown to be an important protagonist in chondrocyte differentiation and cartilage tissue formation processes [ 54 , 55 ]. It was found to be involved in a signalling cascade initiated by KIT (also located in lop-ear associated ROHR) and therefore might support the formation of ear cartilage tissue as well.…”
Section: Discussionmentioning
confidence: 99%
“…The INPPL1 gene encodes SHIP2 protein that plays an important role in chondrocytes during endochondral ossification and differentiation. 19 Variants in INPLL1 gene have been reported to be the genetic cause in several cases of opsismodysplasia and one case of Schneckenbecken dysplasia (see Table 1). Presence of INPPL1 mutation-negative cases of opsismodysplasia and known molecular defects in SLC35D1 gene causing Schneckenbecken dysplasia should suggest genetic heterogeneity of both disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The INPPL1 gene encodes SHIP2 protein that plays an important role in chondrocytes during endochondral ossification and differentiation 19 . Variants in INPLL1 gene have been reported to be the genetic cause in several cases of opsismodysplasia and one case of Schneckenbecken dysplasia (see Table 1).…”
Section: Discussionmentioning
confidence: 99%